A Covalent p97/VCP ATPase Inhibitor can overcome resistance to CB-5083 and NMS-873 in colorectal cancer cells - Zhang, Gang (Eur J Med Chem, 2021)
Small-molecule inhibitors of p97 are useful tools to study p97 function. Human p97 is an important AAA ATPase due to its diverse cellular functions and implication in mediating the turnover of proteins involved in tumorigenesis and virus infections. Multiple p97 inhibitors identified from previous high-throughput screening studies are thiol-reactive compounds targeting Cys522 in the D2 ATP-binding domain. Thus, these findings suggest a potential strategy to develop covalent p97 inhibitors. We first used purified p97 to assay several known covalent kinase inhibitors to determine if they can inhibit ATPase activity. We evaluated their selectivity using our dual reporter cells that can distinguish p97 dependent and independent degradation. We selected a β-nitrostyrene scaffold to further study the structure-activity relationship. In addition, we used p97 structures to design and synthesize analogues of pyrazolo[3,4-d]pyrimidine (PP). We incorporated electrophiles into a PP-like compound 17 (4-amino-1-tert-butyl-3-phenyl pyrazolo[3,4-d]pyrimidine) to generate eight compounds. A selective compound 18 (N-(1-(tert-butyl)-3-phenyl-1H-pyrazolo[3,4-d]pyrimidin-4-yl)acrylamide, PPA) exhibited excellent selectivity in an in vitro ATPase activity assay: IC(50) of 0.6 μM, 300 μM, and 100 μM for wild type p97, yeast Cdc48, and N-ethylmaleimide sensitive factor (NSF), respectively. To further examine the importance of Cys522 on the active site pocket during PPA inhibition, C522A and C522T mutants of p97 were purified and shown to increase IC(50) values by 100-fold, whereas replacement of Thr532 of yeast Cdc48 with Cysteine decreased the IC(50) by 10-fold. The molecular modeling suggested the hydrogen bonds and hydrophobic interactions in addition to the covalent bonding at Cys522 between WT-p97 and PPA. Furthermore, tandem mass spectrometry confirmed formation of a covalent bond between Cys522 and PPA. An anti-proliferation assay indicated that the proliferation of HCT116, HeLa, and RPMI8226 was inhibited by PPA with IC(50) of 2.7 μM, 6.1 μM, and 3.4 μM, respectively. In addition, PPA is able to inhibit proliferation of two HCT116 cell lines that are resistant to CB-5083 and NMS-873, respectively. Proteomic analysis of PPA-treated HCT116 revealed Gene Ontology enrichment of known p97 functional pathways such as the protein ubiquitination and the ER to Golgi transport vesicle membrane. In conclusion, we have identified and characterized PPA as a selective covalent p97 inhibitor, which will allow future exploration to improve the potency of p97 inhibitors with different mechanisms of action.